DETERMINING MATERIAL AND FREE VIBRATION VALUES OF HISTORICAL STRUCTURES BY WAY OF SAMPLING - Kocak, Ali; Zengin, Basak (DOLNOSLASKIE WYDAWNICTWO EDUKACYJNE-DWE, 2012)
It is necessary to know the behavior of historical structures under earthquakes and external loads in terms of their physical and mechanical properties. Although historical structures are unique with respect to either material or load bearing systems, their designs are affected by the architectural and construction methods of their construction era. Thus, the period of construction and the manufacturing and design methods of that period must be known to identify and model the structures and monuments. However, some uncertainities in the modeling of historical structures are; accuracy of these models and obtaining behavior of structures during earthquakes using numerical models. Identification of the characteristic properties of materials used in such structures is convenient in modeling. On the other hand it does not fully reflect the earthquake behavior of the building. Determining the vibration periods of the structure, and approximating them to experimental periods provides accuracy in modeling. In this study, material behavior in the modeling of historical structures and several ways of determining structure periods are emphasized. The materials used in historical structures especially those located in Istanbul, Turkey and the characteristic values of these materials are addressed. Additionally, vibration periods and the modeling of these structures are examined.
Keywords: Construction & Building Technology; Engineering